Pro-Arrhythmic Ventricular Remodeling Is Associated With Increased Respiratory and Low-Frequency Oscillations of Monophasic Action Potential Duration in the Chronic Atrioventricular Block Dog Model - Sprenkeler, David Jaap; Beekman, Jet D. M.; Bossu, Alexandre; Dunnink, Albert; Vos, Marc A. (Frontiers in Physiology, 2019)
In addition to beat-to-beat fluctuations, action potential duration (APD) oscillates at 1.) a respiratory frequency and 2.) a low frequency (< 0.1 Hz), probably caused by bursts of sympathetic nervous system discharge. This study investigates whether ventricular remodeling in the chronic AV block (CAVB) dog alters these oscillations of APD and whether this has consequences for arrhythmogenesis. We performed a retrospective analysis of 39 dog experiments in sinus rhythm (SR), acute AV block (AAVB) and after 2 weeks of chronic AV block. Spectral analysis of left ventricular monophasic action potential duration (LV MAPD) was done to quantify respiratory frequency (RF) power and low frequency (LF) power. Dofetilide (0.025mg/kg in 5 minutes) was infused to test for inducibility of Torsade de Pointes (TdP) arrhythmias. RF power was significantly increased at CAVB compared to AAVB and SR (log[RF] of -1.13 ± 1.62 at CAVB versus log[RF] of -2.82 ± 1.24 and -3.29 ± 1.29 at SR and AAVB, respectively, p<0.001). LF power was already significantly increased at AAVB and increased even further at CAVB (-3.91 ± 0.70 at SR, versus -2.52 ± 0.85 at AAVB and -1.14 ± 1.62 at CAVB, p<0.001). In addition, LF power was significantly larger in inducible CAVB dogs (log[LF] -0.6 ± 1.54 in inducible dogs vs. -2.56 ± 0.43 in non-inducible dogs, p < 0.001). In conclusion, ventricular remodeling in the CAVB dog results in augmentation of respiratory and low frequency oscillations of LV MAPD. Furthermore, TdP-inducible CAVB dogs show increased LF power.